Intention to Use Mobile Payment System: A Case of Developing Market by Ethnicity - Hiram, Ting; Yusman, Yacob; Lona, Liew; Wee, Ming Lau (Elsevier Ltd., 2016)
Due to the rapid rise of communication technologies, mobile payment system has emerged as a popular method to facilitate payment transactions. Notwithstanding its widespread use, what affects intention of mobile users towards paying through mobile phones and why in the context of developing market remain largely unanswered. Moreover, little is done to articulate the implication of ethnicity on payment behaviours. By using the theory of planned behaviour as the underlying basis, this study aims to investigate the effects of attitude, subjective norm and perceived behavioural control on intention towards the use of mobile payment system among Malays and Chinese in Malaysia. Beliefs are included as antecedent variables in the framework so as to enhance understanding of the subject matter. Quantitative approach by means of questionnaire-based survey is adopted. 450 copies of questionnaire are distributed throughout the country, and 311 usable copies are subsequently collected. In addition to descriptive analysis, multiple linear regression and independent sample t -test are utilized to perform tests of association and difference. The findings show that attitude, subjective norm and perceived behavioural control are positively predicted by their respective belief factors, and they also have positive effect on intention to use mobile payment system. However, subjective norm and perceived safety are found to be significantly different between Malays and Chinese. As a result, the intention of the two ethnic groups is also found to be different. The study highlights the need to understand what contributes to users’ intention towards mobile payment system in developing markets. It also underlines the importance to know what is shared and what is not in multi-ethnic and cultural countries like Malaysia. It therefore provides insights into effective service operation and marketing of mobile payment system so as to utilize such communication technology and achieve service excellence.